Cardiovascular safety of Janus kinase inhibitors: A pharmacovigilance study from 2012–2023 - Xiaoyan Zhong; Jianchun Luo; Yuexi Huang; Shurong Wang; Yilan Huang (PLoS ONE, 2025)
Janus kinase inhibitors (JAKinibs) are increasingly used for autoimmune diseases, prompting concerns about their cardiovascular safety. This study aims to assess the cardiovascular safety of JAKinibs in real-world settings. We conducted a retrospective analysis of FDA Adverse Event Reporting System (FAERS) data from the fourth quarter of 2012 to the second quarter of 2023, focusing on cardiovascular adverse events (AEs) associated with JAKinibs. We used disproportionality analysis to calculate reporting odds ratios (RORs) and identify signals of increased cardiovascular risk. This study identified 13,556 reports of cardiovascular AEs associated with JAKinibs in the FAERS database. Compared to the full database, Baricitinib exhibited significant signals for embolic and thrombotic events (ROR025 = 5.58), ischemic heart disease (ROR025 = 1.56), and cardiac arrhythmias (ROR025 = 1.14). Tofacitinib was associated with the signal for hypertension (ROR025 = 1.05), and upadacitinib was linked to embolic and thrombotic events (ROR025 = 1.23). When compared to TNF-α inhibitors, upadacitinib, baricitinib and tofacitinib showed 7, 6, and 2 positive signals, respectively (all ROR025 > 1). These findings highlight the need for careful cardiovascular monitoring and risk assessment for patients receiving JAKinibs, particularly those with pre-existing cardiovascular risk factors or older age.